Influence of textile effluent on the Reaction, Structure and Properties of (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The transformation of industrial wastes into useful products attracts more researches to work upon for sustainable of natural resources. In this paper, industrial wastes such as treated textile effluent and fly ash were used in the preparation of plain cement concrete with the intention of reducing the environmental pollution caused by these materials. The partially treated textile effluent was used as mixing water and fly ash was used as 30% partial replacement by weight of cement in concrete. The textile effluents were collected after anaerobic treatment and tertiary treatment from textile industry. Class F Fly ash was collected from Mettur thermal power plant. The physical and chemical properties of treated textile effluent were studied. The control concrete was prepared with potable water available in the laboratory. Experimental test was performed for compressive strength of concrete at 28 days. The powdered concrete samples were examined through infrared spectroscopy, X-ray diffraction and scanning electron microscopy to study the microstructure of concrete. The compressive strength test results revealed that anaerobic effluent water (AAE) concrete accomplished higher compressive strength than control concrete. This was also in affirmation with microscopic analysis in which the formations of hydration products were well established when compared to control concrete.